Unpacking Impulsive Buying in Tiktok Live Shopping: The Roles of Influencer Attributes, Interaction Strategies, and Parasocial Relationships - Arum Puspaningtyas; Gancar Candra Premananto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The rise of live commerce through TikTok Shop has transformed consumer behavior patterns, particularly by triggering impulsive purchases through real-time interactions between influencers and audiences. This study aims to analyze the influence of influencer attributes and interaction strategies on parasocial relationships and their impact on perceived quality uncertainty, perceived fit uncertainty, and impulsive buying within the context of TikTok Shop Live. A quantitative research design using Structural Equation Modeling–Partial Least Squares (SEM-PLS) was employed, involving 100 active TikTok Shop Live users as respondents. The results show that influencer attributes and interaction strategies significantly affect the formation of parasocial relationships. Parasocial relationships were also found to reduce perceived quality uncertainty and perceived fit uncertainty, while exerting a strong direct influence on impulsive buying. Additionally, both forms of uncertainty negatively affect impulsive buying, highlighting the cognitive role of consumers in spontaneous purchase decisions. The proposed model explains 67 percent of the variance in impulsive buying, indicating strong predictive power.